2022
DOI: 10.1002/sim.9547
|View full text |Cite
|
Sign up to set email alerts
|

Use of copula to model within‐study association in bivariate meta‐analysis of binomial data at the aggregate level: A Bayesian approach and application to surrogate endpoint evaluation

Abstract: Bivariate meta-analysis provides a useful framework for combining information across related studies and has been utilized to combine evidence from clinical studies to evaluate treatment efficacy on two outcomes. It has also been used to investigate surrogacy patterns between treatment effects on the surrogate endpoint and the final outcome. Surrogate endpoints play an important role in drug development when they can be used to measure treatment effect early compared to the final outcome and to predict clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…This method is very similar to a double bootstrap approach which has been previously used to, for example, estimate the correlation with an interval used as an input in the multivariate meta-analysis of mixed outcomes. 22,23 3.4 | The infinite population method (STC-IP)…”
Section: The Multiple Imputation Methods (Stc-mi)mentioning
confidence: 99%
See 1 more Smart Citation
“…This method is very similar to a double bootstrap approach which has been previously used to, for example, estimate the correlation with an interval used as an input in the multivariate meta-analysis of mixed outcomes. 22,23 3.4 | The infinite population method (STC-IP)…”
Section: The Multiple Imputation Methods (Stc-mi)mentioning
confidence: 99%
“…This can have implications for the stability of the standard error, as we will illustrate in our simulation study in Section 5. This method is very similar to a double bootstrap approach which has been previously used to, for example, estimate the correlation with an interval used as an input in the multivariate meta‐analysis of mixed outcomes 22,23 …”
Section: Four Different Methods For Stcmentioning
confidence: 99%
“…However, modeling jointly non-normal outcomes, such as binomial responses, would require transforming data, which can lead to biased results [12]. Papanikos et al carried out a simulation study showing that when the within-study correlation is weak, a multivariate meta-analysis model with independent binomial likelihoods is preferable [13]. An exploratory analysis of the BSRBR-RA dataset, estimating the within-study correlation using the bootstrapping approach [14,15], showed that the within-study correlation between the treatment effects for the two lines of therapy transformed onto the log odds ratio (OR) scale was close to zero.…”
Section: Bivariate Network Meta-analysismentioning
confidence: 99%
“…An exploratory analysis of the BSRBR-RA dataset, estimating the within-study correlation using the bootstrapping approach [14,15], showed that the within-study correlation between the treatment effects for the two lines of therapy transformed onto the log odds ratio (OR) scale was close to zero. We, therefore, adapted the approaches to multivariate/bivariate NMA by Achana et al [16] and Bujkiewicz et al [17] by assuming independent binomial likelihoods at the within-study level, as in Papanikos et al [13], to model the proportions of responders to treatment in each line of therapy. To predict treatment effects in the second line when data are only available for the therapy in first line, additional assumptions of exchangeability needed to be made, where instead of placing prior distributions on basic parameters, we added another level of hierarchy to the model as in Bujkiewicz et al [17].…”
Section: Bivariate Network Meta-analysismentioning
confidence: 99%